Identification of Target Gene and Interacting Protein of Two LaSCL6 Alternative Splicing Variants Provides Novel Insights into Larch Somatic Embryogenesis - Qiao-Lu Zang; Zha-Long Ye; Li-Wang Qi; Wan-Feng Li (Plants)
Somatic embryogenesis is valuable for clonal propagation and genetic improvement, and it also serves as an ideal system for studying plant development mechanisms. In Larix kaempferi, microRNA171 and its target gene L. kaempferi SCARECROW-LIKE6 (LaSCL6), which has two alternative splicing variants, can regulate somatic embryogenesis; however, the underlying molecular mechanism is still unknown. In this study, we overexpressed these two LaSCL6 variants in Oryza sativa and Arabidopsis thaliana and then used the RNA-Seq method to screen genes from O. sativa and A. thaliana, whose expression patterns are related to those of LaSCL6 variants. The screened genes were then used to search L. kaempferi proteins to identify the candidate target genes of LaSCL6. After yeast one-hybrid and dual- luciferase transcriptional activity assays, cytochrome P450, family 89, subfamily A, polypeptide 5 (CYP89A5), and wall-associated receptor kinase-like 20 (WAKL20) were confirmed to be the target genes of LaSCL6-var1; in addition, WAKL20 and UDP-glycosyltransferase 85A3 (UGT85A3) were confirmed to be the target genes of LaSCL6-var2. Moreover, APETALA2-like protein 2, a transcription factor from the AP2/ERF family, was shown to interact with LaSCL6-var1 and LaSCL6-var2. Taken together, our results suggest a regulatory network of miR171-LaSCL6. The findings presented here not only provide novel insights into the regulation of the miR171-LaSCL6 module but also explain the mechanism underlying larch somatic embryogenesis and other biological processes.